GlyXalign: High‐throughput migration time alignment preprocessing of electrophoretic data retrieved via multiplexed capillary gel electrophoresis with laser‐induced fluorescence detection‐based glycoprofiling. Issue 16 (8th July 2013) - Behne, Alexander; Muth, Thilo; Borowiak, Matthias; Reichl, Udo; Rapp, Erdmann; Guttman, Andras
<x xml:space="preserve">Abstract</x> Glycomics has become a rapidly emerging field and monitoring of protein glycosylation is needed to ensure quality and consistency during production processes of biologicals such as therapeutic antibodies or vaccines. Glycoanalysis via multiplexed CGE with LIF detection (xCGE‐LIF) represents a powerful technique featuring high resolution, high sensitivity as well as high‐throughput performance. However, sample data retrieved from this method exhibit challenges for downstream computational analysis due to intersample migration time shifts as well as stretching and compression of electropherograms. Here, we present glyXalign, a freely available and easy‐to‐use software package to automatically correct for distortions in xCGE‐LIF based glycan data. We demonstrate its ability to outperform conventional algorithms such as dynamic time warping and correlation optimized warping in terms of processing time and alignment accuracy for high‐resolution datasets. Built upon a set of rapid algorithms, the tool includes an intuitive graphical user interface and allows full control over all parameters. Additionally, it visualizes the alignment process and enables the user to readjust misaligned results. Software and documentation are available at http://www.glyxera.com.